Ecosystem restoration: challenges and opportunities for India. Issue 3 (18th February 2021) - Singh, Kripal; Singh, Rana Pratap; Tewari, Shri Krishna
Abstract : Ninety‐six million hectares of degraded land, unprecedented loss of biodiversity, and extreme climatic events are the key ecological challenges for India. Offering livelihood opportunities to millions of workers who migrated to their villages and recovery from economic crisis due to covid‐19 pandemic have emerged as the biggest socio‐economic challenges for the country. A framework of different policies and strategies are in place to overcome these ecological and socio‐economic challenges. But they are loosely interconnected with independent aims and involvement of different governments' institutions and departments. This article, therefore, here briefs challenges and shows how aiming at ecosystem restoration and biodiversity conservation through these policies can provide a cost‐effective, efficient, and sustainable way for India to overcome its ecological and socio‐economic challenges.